Sodium chloride intake: is lower always better? - Lambers Heerspink, Hiddo J.; Ritz, Eberhard (Journal of the American Society of Nephrology, 2012)
Current treatment of kidney disease is not completely satisfactory, particularly when initiated in the late stages of renal progression. There is an urgent need for additional interventions, especially reduction of salt intake, which is rather high in the Western world. In this commentary we provide a critical assessment of post hoc analyses of recent interventional and observational studies on the effect of salt intake on renal and cardiovascular outcomes. To evaluate the mechanisms and safety of reduced salt intake, studies speciﬁcally designed to assess salt intake as an endpoint are needed. This approach will have implications for health care policies and labeling of the salt content of purchased foods.